2013 46th Hawaii International Conference on System Sciences 2013
DOI: 10.1109/hicss.2013.615
|View full text |Cite
|
Sign up to set email alerts
|

Writing on the Wall: An Online "Community" of YouTube Patrons as Communication Network or Cyber-Graffiti?

Abstract: Scholars continue to debate the social functions of YouTube as an online platform; some pointing to emergence of community [21] while others describing it as an asocial extension of a television screen [7]. This paper argues for three types of participation online: passive, active and interactive. Focusing on one particular YouTube site, the authors engage in a multi-method exploration of the content of communication (using thematic analysis) as well as interaction patterns (emerging through a network analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Participation on YouTube was mostly of a passive kind with a small proportion of users participating actively and even fewer interacting with others. As can be expected, interactive participants who pursue social contacts are more likely to perceive YouTube as an online community, whereas non-interactive and passive users use it as a channel similar to television (Shoham et al, 2013).…”
Section: Types Of Participationmentioning
confidence: 75%
See 2 more Smart Citations
“…Participation on YouTube was mostly of a passive kind with a small proportion of users participating actively and even fewer interacting with others. As can be expected, interactive participants who pursue social contacts are more likely to perceive YouTube as an online community, whereas non-interactive and passive users use it as a channel similar to television (Shoham et al, 2013).…”
Section: Types Of Participationmentioning
confidence: 75%
“…In a study by Shoham, Arora, and Al-Busaidi (2013) focusing on interaction around a YouTube video, the researchers explored how socially-targeted and interactive the commenting was, in other words, whether active participants posted general comments or targeted their comments to certain persons. Shoham et al (2013) identified three different types of content consumption: interactive consumption that employs YouTube as an interactive tool; passive consumption that takes place when users passively view the content similarly to television; and active consumption that happens when users actively comment on the content but do not address their comments to other users. Those whose interactions are more targeted to specific others, for example in the form of chatting and messaging in order to create and maintain relationships, are found to be more important for community formation, as interactive users form subgroups and tend to be more community-oriented (Shoham et al, 2013).…”
Section: Types Of Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…For these members, Imgur participation has less to do with building a shared identity and more to do with fun (excerpt 18). Studies on YouTube, which provides similar affordances for entertainment without requiring interaction, show that while users may be highly active in commenting, community feelings only arise among the small proportion of users who develop relationships with others ( Rotman et al, 2009;Shoham, Arora & Al-Busaidi, 2013). These findings suggest that entertainment sites such as Imgur and YouTube give space for many kinds of experiences of participation, some community-oriented and others less so.…”
Section: Discussionmentioning
confidence: 99%
“…Just like YouTube users are mostly passive, only a part of them actively participates, and their participation in active interaction with others is even lower. Interactive participants pursuing social relationships are more likely to view YouTube as an online community, while non-interactive and passive users use YouTube as a TV-like channel [16]. In addition, participation in virtual communities includes passively viewing and actively posting [17], or classified users as content contributors and content consumers [18].…”
Section: Passive Users Vs Lurkersmentioning
confidence: 99%